1999
DOI: 10.1159/000024979
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus C/Hepatitis G Virus

Abstract: Hepatitis G virus (HGV) is a positive, single-strand RNA virus that has been classified in the family Flaviviridae. The 5′-untranslated region (UTR) of the HGV genome is lengthy and does not share any significant primary and secondary RNA structures with the 5′-UTR of hepatitis C virus (HCV). The internal ribosome entry site has extraordinarily weak activity. The HGV genome does not seem to encode a nucleocapside protein analogous to HCV. Blood-borne transmission is presumed to be the commonest mode of transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Characterization of PBMC subsets identified the CD4 ϩ T cells as the cells supporting GBV-C replication. Although early studies suggested that GBV-C replicates in the liver, most reported studies indicate that GBV-C is not hepatotropic (20,24). Our inability to demonstrate infection of HepG2 cells is consistent with this, although we were also unable to demonstrate persistent replication in the CD4 ϩ T-cell line (MOLT-4).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of PBMC subsets identified the CD4 ϩ T cells as the cells supporting GBV-C replication. Although early studies suggested that GBV-C replicates in the liver, most reported studies indicate that GBV-C is not hepatotropic (20,24). Our inability to demonstrate infection of HepG2 cells is consistent with this, although we were also unable to demonstrate persistent replication in the CD4 ϩ T-cell line (MOLT-4).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown lately that HIV patients co-infected with GBV-C have a lower mortality than other HIV-infected patients [Tillmann et al, 2001;Xiang et al, 2001]. The virus replicates in haemapoetic cells but apparently not in hepatocytes, and we will refer to the virus as GBV-C in this paper [Kiyosawa and Tanaka, 1999;Xiang et al, 2001;Tucker and Smuts, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that co-infection HGV with HBV aggravates the defeat a liver affection, whereas in combination with HIVinfection have a beneficial effect on its clinical current (Chams et al, 2003;Lau et al, 1999;Muerhoff, Tillmann et al, 2003). According to some data HGV does not influence on the other hepatitis development (Enomoto, Shuhei et al, 1998;Kiyosawa and Tanaka, 1999). At the same time another group of Japanese researchers showed that current of hepatitis C in combination with HGV-infection has a mild form (Tanaka, Alter et al 1996;Karayiannis, Hadziannis et al, 1997).…”
Section: Introductionmentioning
confidence: 99%